Perancangan Sistem Informasi Pemantauan Kesehatan dan Status Gizi Ibu Hamil Cegah Stunting - Faizah Wardhina; Dwidya Poernareksa; Rina Gunarti (Politeknik Negeri Jember, 2024)
The incidence of stunting in Indonesia according to data from the 2021 Indonesian Nutrition Status Study (SSGI) is 24.4%, still far from the national target of 14% in 2024. One way to prevent stunting is to provide nutritional and health services to pregnant women. When examining pregnant women, recording is one way to monitor the health of pregnant women. All pregnancy examination results are manually recorded in the KIA book and the pregnant mother register book. This manual recording system can cause the search for pregnant women's health history to be slow. Apart from that, there is a possibility that the KIA book was left at home. This research aims to design an information system for monitoring the health and nutritional status of pregnant women. This research used research and development method, and system design using the waterfall method. The results are a system for monitoring the health and nutritional status of pregnant women which can be used to record examination results during pregnancy to prevent stunting. Suggestions to future researchers are to develop this information system so that it can be utilized optimally for stunting prevention.